Resepsi Pembaca terhadap Isu Perselingkuhan Nissa Sabyan dan Ayus Sabyan di Tribunnews.com - Ahmad Khairul Nuzuli Ahmad Khairul Nuzuli; Ivan Sunata (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2022)
The pelakor case is one of the things that is viral in the media today, including the case of the affair of Nissa Sabyan and Ayus Sabyan. The concept of pelakor is one of the terms that is viralized by the mass media. This study aims to see how the readers interpret the affair issue of Nissa Sabyan and Ayus Sabyan in Tribunnews.com. This research uses descriptive qualitative type using reception analysis. The results showed that the majority of informants agreed with the pelakor labeling given by the media. On the other hand, the informants agree more that Nissa Sabyan and Ayus Sabyan are jointly responsible for their case. The opinion of the informant is influenced by the experience and environment in which the informant is located.